(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2016)
This paper looks into the function of human style relationship facets when applied to brands through a brand love relationship. Methodologically, this investigation defined two groups of respondents (from a questionnaire applied to 224 respondents): those who self-reported a brand love relationship and those who did not. These groups were compared through a Likert questionnaire in order to find evidence of key human relationship facets that run along a brand love relationship, such as the self-ideal and positive psychology. Although, we did not find significant effects of the three key variables, the descriptive statistics showed higher averages where expected.